2005
DOI: 10.1152/japplphysiol.00254.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tidal volume and respiratory frequency on lung lymph flow

Abstract: Ventilation (V) increases lung lymph flow (Ql), but the separate effects of tidal volume (Vt) and frequency (f) and the role of V-induced changes in edema formation are poorly understood. An isolated, in situ sheep lung preparation was used to examine these effects. In eight sheep with f = 10 min(-1), results obtained during 30-min periods with Vt = 5 or 20 ml/kg were compared with values obtained during bracketed 30-min control periods (Vt = 12.5 ml/kg). Eight other sheep with constant Vt (12.5 ml/kg) were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Consistent with this role, a hallmark sign of generalized loss of lymphatic function is tissue edema (62), and lymphatic function is required for fluid drainage in the developing lung to enable neonatal lung inflation (2). Although large animal studies using short-term catheter-based approaches have demonstrated that lymphatic flow in the lung may be dynamic (21,22), pulmonary edema can also be considered a consequence of imbalanced Starling forces in the alveolar blood capillaries rather than loss of lung lymphatic function (63). Our studies of CLEC2-deficient lungs provide genetic insight into the long-term role of lymphatic vessels in the management of fluid homeostasis in the mature lung.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this role, a hallmark sign of generalized loss of lymphatic function is tissue edema (62), and lymphatic function is required for fluid drainage in the developing lung to enable neonatal lung inflation (2). Although large animal studies using short-term catheter-based approaches have demonstrated that lymphatic flow in the lung may be dynamic (21,22), pulmonary edema can also be considered a consequence of imbalanced Starling forces in the alveolar blood capillaries rather than loss of lung lymphatic function (63). Our studies of CLEC2-deficient lungs provide genetic insight into the long-term role of lymphatic vessels in the management of fluid homeostasis in the mature lung.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologic studies of collecting lymphatics from the limb and mesentery have demonstrated that active SMC contraction and valve activity are coordinated to create waves of forward movement of lymph (16)(17)(18)(19). In the lung, however, physiologic studies using catheter-based measurement of pulmonary lymph flow in anesthetized large animals have suggested that extrinsic forces such as changes in thoracic pressure associated with respiration may play a more central role (3,4,(20)(21)(22).…”
Section: Resultsmentioning
confidence: 99%
“…Levine et al (32) have shown that lymph flow increased only 10% with normobaric hypoxia in sheep, whereas Martin et al (35) found that lymph flow was increased by ϳ40% in dogs when exposed to hypoxia. Increases in ventilation are thought to lead to an increase in lung lymph flow (46). In the present study, we were able to monitor changes in ventilation for the entire night of hypoxic exposure using the LifeShirt monitoring system (Vivometrics, Ventura, CA).…”
Section: Discussionmentioning
confidence: 95%
“…Levine et al have shown that lymph flow increased only 10% with normobaric hypoxia in sheep, while Martin et al found that lymph flow was increased by approximately 40% in dogs when exposed to hypoxia (Levine et al, 1988; Martin et al, 1986). Increases in ventilation are also lead to an increase in lung lymph flow (Pearse et al, 2005). And a previous study by our group showed a significant increase in ventilation with exposure to normobaric hypoxia (Snyder et al, 2006a).…”
Section: Discussionmentioning
confidence: 99%